State’s Authority Concerning Health Protection in Ordinary Times and During Epidemics - Jacek Meller (Studia Ecologiae et Bioethicae)
Life and health as fundamental matters are major concerns for every human being. To this end, he / she should be assisted by the community in which they live. If the foundation of social life is the personalistic principle, the recognition of the primacy of the dignity of the person, among other values, is constructed on the principles of subsidiarity and solidarity. It is the role of the healthcare institution to create such conditions, in which the safest and the most effective methods of treatment and prevention are available, and the individual can consciously select which of these realises his or her good to the greatest extent, in accordance with the recognised hierarchy of values, the accepted worldview, and life goals. The aim of this article is to analyse the relationship between the community and the individual, in the field of healthcare, under normal conditions and during epidemics. The existence of specific threats may suggest that exceptions to the fundamental rules of social life: autonomy, subsidiarity, and social solidarity, are permissible. However, the recognition of the fundamental value of the dignity of the person, requires the community to apply the same rules as in normal times, although many activities of public institutions are intensified in times of more serious danger.